Questions and Controversies in the Clinical Application of Tyrosine Kinase Inhibitors to Treat Patients with Radioiodine-Refractory Differentiated Thyroid Carcinoma: Expert Perspectives - Verburg, Frederik A.; Amthauer, Holger; Binse, Ina; Brink, Ingo; Buck, Andreas; Darr, Andreas; Dierks, Christine; Koch, Christine; König, Ute; Kreissl, Michael C.; Luster, Markus; Reuter, Christoph; Scheidhauer, Klemens; Willenberg, Holger Sven; Zielke, Andreas; Schott, Matthias (Hormone and Metabolic Research, 2021)
Notwithstanding regulatory approval of lenvatinib and sorafenib to treat radioiodine-refractory differentiated thyroid carcinoma (RAI-R DTC), important questions and controversies persist regarding this use of these tyrosine kinase inhibitors (TKIs). RAI-R DTC experts from German tertiary referral centers convened to identify and explore such issues; this paper summarizes their discussions. One challenge is determining when to start TKI therapy. Decision-making should be shared between patients and multidisciplinary caregivers, and should consider tumor size/burden, growth rate, and site(s), the key drivers of RAI-R DTC morbidity and mortality, along with current and projected tumor-related symptomatology, co-morbidities, and performance status. Another question involves choice of first-line TKIs. Currently, lenvatinib is generally preferred, due to greater increase in progression-free survival versus placebo treatment and higher response rate in its pivotal trial versus that of sorafenib; additionally, in those studies, lenvatinib but not sorafenib showed overall survival benefit in subgroup analysis. Whether recommended maximum or lower TKI starting doses better balance anti-tumor effects versus tolerability is also unresolved. Exploratory analyses of lenvatinib pivotal study data suggest dose-response effects, possibly favoring higher dosing; however, results are awaited of a prospective comparison of lenvatinib starting regimens. Some controversy surrounds determination of net therapeutic benefit, the key criterion for continuing TKI therapy: if tolerability is acceptable, overall disease control may justify further treatment despite limited but manageable progression. Future research should assess potential guideposts for starting TKIs; fine-tune dosing strategies and further characterize antitumor efficacy; and evaluate interventions to prevent and/or treat TKI toxicity, particularly palmar-plantar erythrodysesthesia and fatigue.
Keywords: multi-kinase inhibitors; treatment initiation and discontinuation; dosing; second-line therapy; lenvatinib; sorafenib